Comprehensive Repertoire of Foldable Regions within Whole Genomes - Faure, Guilhem; Callebaut, Isabelle (PLOS Computational Biology, 2013)
Author Summary Spontaneous or induced folding into a specific 3D structure is a key property of proteins to perform their biological functions. Folded 3D structures of proteins perform specific functions, including interactions with other proteins. Intrinsically disordered regions also mediate interaction, gaining structure only when bound to a target protein. In both cases, hydrophobicity generally plays a major role in the protein segment “foldability”. Here, we developed an original procedure to identify foldable segments from only the information of a single amino acid sequence and to explore protein structures at a proteomic scale. Our approach goes beyond the simple consideration of mean hydrophobicity, by including the secondary structure information through the use of a two-dimensional transposition of the sequence. The developed procedure, combined with disorder predictors, may facilitate the specific identification of small segments that undergo coupled folding and binding. Combined with the analysis of specific domain databases, it also highlights orphan foldable segments, which remain yet uncharacterized.